Tetraguanidinium bis[citrato(3−)]cuprate(II) dihydrate - Al-Dajani, Mohammad T. M. (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, (CH(6)N(3))(4)[Cu(C(6)H(5)O(7))(2)]·2H(2)O, contains one-half of a centrosymmetric Cu(II) complex anion, two guanidinium cations and a water molecule. The Cu(II) ion, lying on a crystallographic inversion center, is hexacoordinated with two citrate anions in a distorted octahedral geometry. An intramolecular O—H⋯O hydrogen bond generates an S(6) ring motif. In the crystal structure, molecules are linked into a three-dimensional framework by intermolecular N—H⋯O and O—H⋯O hydrogen bonds.